Biomechanical rationale of coronary artery bypass grafting of multivessel disease. Issue 3 (17th February 2016) - Grishina, Olga A.; Kirillova, Irina V.; Glukhova, Olga E.
Abstract : The biomechanical model of human coronary arteries was modified for improving the quality of diagnosis and surgical treatment for coronary heart disease. The problem of hemodynamics in the left coronary artery with multivessel bed disease – 45% stenosis of the anterior descending branch and 75% stenosis of the circumflex branch – was particularly considered. Numerical simulation of the coronary arterial bypass of the main trunk was carried out to estimate the functional condition of the coronary arteries after restoring myocardial blood supply by surgery.